(untitled) (Equilibrium: Jurnal Pendidikan, 2019)
Every society has a norm as a life guide like tongkonan meaning. The purpose of the study is to reveal the history of the formation and the impact of tongkonan as a social phenomenon. The type of research conducted is qualitative research. Informants are determined on the basis of the characteristics of informants that are defined as community members, community leaders, customary leaders. Data collection techniques are observation, documentation and interview. Data analysis techniques through various stages of data reduction, data presentation and conclusion, while the technique of data validity using triangulation of sources, time and techniques. The results showed the history of the process of formation of ongkonan lasted for a long time influenced by the factors of closeness and similarity. Some individuals or communities have a tongkonan due to social customary control factors. Positive implications of Tongkonan meaning are those that have rules, social solidarity, places of need, mutual cooperation, whereas the negative implication is tend to neglect education. Keywords: Social Meaning, Tongkonan, Toraja.